ENGLISH COMPOUND WORDS USED IN THE JAKARTA POST HEALTH COLUMN ON THIRD WEEK OF APRIL 2020 - Felix Stefani Sisvinda (PROJECT (Professional Journal of English Education), 2021)
This study aims to describe the formation and the meaning of compound words that related to COVID-19 pandemics used in The Jakarta Post’s Health Column Article on Third Week of April 2020. There are two research question in this study: (1) What are the type of COVID-19 compound words and their lexical categories found in The Jakarta Post’s Health Column Article on Third Week of April 2020, and (2) How does those related COVID-19 compound words create meaning. To answer the research question, the writer uses the theory of morphology and semantics. The findings showed that there are 26 compound words in The Jakarta Post’s Health Column on the third week of April 2020. Based on the type of compound words, there are 86.4% compound noun, 11.5% compound adjective, and 3.9% compound verb. The most dominant lexical category is from compound nouns which are Noun+Noun and Adjective + Noun.  Based on the meaning of compound words, there are are 80.76% endocentric compounds and 19.24% exocentric compounds.Keywords: Compound words, COVID-19, Morphology, Semantics